EFEITOS DA RADIAÇÃO GAMA DURANTE O ARMAZENAMENTO DA FARINHA DE BAGAÇO DE MAÇÃ - Ito, Vivian Cristina (2015)
The apple is a very popular fruit because of its aroma, flavor and attractive look, its consumption is related to several benefits to human health. With industrialization, a residue of juice extraction is generated, the apple pomace, with similar characteristics of nutrients and bioactive compounds that fruit. This apple pomace after stabilization becomes a by-product with excellent biotechnological applications. The positive effects of irradiation in food has been exploration, especially in increasing the useful life of the product. This study aimed to evaluate the effects of gamma radiation on the physicochemical characteristics, thermogravimetric, microstructural and microbiological, phenolic compounds and antioxidant potential of apple cake meal, for nine months of storage, with the help of multivariate techniques such as analysis Principal Components (PCA) and Hierarchical Cluster Analysis (HCA). Gamma radiation and the storage period did not influence the parameters of lipid, sucrose, fructose and ashes. Reducing sugars were not affected by the irradiation and the dose of 1 kGy remained stable during the storage period. The glucose was stable from the third month, and the highest levels were found at a dose of 2 kGy. The mineral calcium levels were higher in the irradiated samples. The dietary fiber content of the irradiated samples resulted in lower values compared to the control sample, but remained within the contents found in the literature. The irradiated samples were stable during storage for protein, lipid, dietary fiber, total reducing sugar, minerals K, Zn, Fe and Mn. The Phlorizin was the phenolic compound that remained constant levels during the search. Chlorogenic acid and its class hydroxycinnamic acids increased proportionally with time in the irradiated samples. The chemometric approach is effective to facilitate the visualization of samples of apple cake meal, the physical-chemical parameters and by HCA, the phenolic compounds were separated into three groups, the first characterized in that only samples without irradiation, the Then, samples with 2 kGy and third represent characterized by a dose of 1 kGy. Thermogravimetry curves with four major mass loss in consecutive reactions. In the hotomicrographs, there was an organic material composition and heterogeneous, with agglomerates of particles which have irregular shapes and sizes. From a microbiological point of view the dose of 2 kGy was lethal to the inhibition of yeasts and molds to the end of the study. This raw material is a great source of fiber and can be applied to products with high added value, aiming economy and reducing the environmental impact.